1969
DOI: 10.2466/pr0.1969.25.1.220
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Desensitization of Snake-Avoidance under Two Conditions of Suggestion

Abstract: Two groups of Ss received systematic desensitization for “snakephobia.” 9 Ss were led to expect anxiety reduction from desensitization; another 9 were not. Changes in snake-avoidance for these two groups were compared with changes displayed by 9 Ss who received no treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1970
1970
1979
1979

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The predictive validity of expectancy state has been reported by Krause, Fitzsimmons, and Wolf (1969), Leitenberg, Agras, Barlow, andOliveau (1969), Oliveau, Agras, Leitenberg, Moore, andWright (1969), Oliveau (1969), Marcia, Rubin, and Efran (1969), McGlynn, Mealiea, and Nawas (1969), and McGlynn, Reynolds, and Linder (1971b.…”
Section: Expectancy Statementioning
confidence: 64%
See 2 more Smart Citations
“…The predictive validity of expectancy state has been reported by Krause, Fitzsimmons, and Wolf (1969), Leitenberg, Agras, Barlow, andOliveau (1969), Oliveau, Agras, Leitenberg, Moore, andWright (1969), Oliveau (1969), Marcia, Rubin, and Efran (1969), McGlynn, Mealiea, and Nawas (1969), and McGlynn, Reynolds, and Linder (1971b.…”
Section: Expectancy Statementioning
confidence: 64%
“…These two points apply also to the study by McGlynn et al (1969). While desensitization alone did not produce significant improvement over no treatment, desensitization plus high-expectancy instructions did.…”
Section: Conditions Under Which the Expectancy Effect Has Been Demons...mentioning
confidence: 67%
See 1 more Smart Citation
“…5 5 In the studies summarized above, a comparison was made between a group undergoing a behavior therapy procedure defined as therapy and a group undergoing the same procedure defined as something other than therapy (e.g., an experiment in imagination or a control procedure). A separate series of studies (Cataldo, 1970;Howlett & Nawas, 1971;Lomont & Brock, 1971;McGlynn, 1972;McGlynn & Mapp, 1970;McGlynn, Mealiea, & Nawas, 1969;McGlynn, Reynolds, & Linder, 1971 b;McGlynn & Williams, 1970;Woy & Efran, 1972) has examined the effects of subjects' expectations in a different way. In these studies desensitization was always defined to the subjects as a therapy.…”
Section: Attitudes and Expectancies In Hypnosis And Behavior Therapymentioning
confidence: 97%
“…In one approach, subjects are provided with a general therapeutic orientation while instructional manipulations attempt to influence their expectations regarding treatment outcome. In general, these studies have demonstrated small between-group differences which usually fail to attain statistical significance (Lomont & Brock, 1971;McGlynn, 1972;McGlynn & Mapp, 1970;McGlynn, Mealiea, & Nawas, 1969;McGlynn, Reynolds, & Linder, 1971a;McGlynn & Williams, 1970;Woy & Efran, 1972).…”
mentioning
confidence: 99%